BAP31 Promotes Tumor Cell Proliferation by Stabilizing SERPINE2 in Hepatocellular Carcinoma - Zhang, Xiyang; Jiang, Dongbo; Yang, Shuya; Sun, Yuanjie; Liu, Yang; Shi, Jingqi; Hu, Chenchen; Pan, Jingyu; Liu, Tianyue; Jin, Boquan; Yang, Kun (Frontiers in Cell and Developmental Biology, 2020)
Hepatocellular carcinoma (HCC) patients are mostly diagnosed at an advanced stage resulting in systemic therapy and poor prognosis. Therefore, identification of a novel treatment target for HCC is important. B-cell receptor-associated protein 31 (BAP31) has been identified as a cancer/testis antigen; however, BAP31 function and mechanism of action in HCC remain unclear. In this study, BAP31 was demonstrated to be upregulated in HCC and correlated with the clinical stage. BAP31 overexpression promoted HCC cell proliferation and colony formation in vitro and tumor growth in vivo. RNA-seq analysis demonstrated that serpin family E member 2 (SERPINE2) was downregulated in BAP31 knockdown HCC cells. Coimmunoprecipitation and immunofluorescence assays demonstrated that BAP31 directly binds to SERPINE2. Inhibition of SERPINE2 significantly decreased the BAP31-induced cell proliferation and colony formation of HCC cells and phosphorylation of Erk1/2 and p38. Moreover, multiplex immunohistochemistry staining of the HCC tissue microarray showed positive associations between the expression levels of BAP31, SERPINE2, its downstream gene LRP1, and a tumor proliferation marker, Ki-67. Administration of anti-BAP31 antibody significantly inhibited HCC cell xenograft tumor growth in vivo. Thus, these findings suggest that BAP31 promotes tumor cell proliferation by stabilizing SERPINE2 and can serve as a promising candidate therapeutic target for HCC.